Strategi Pembelajaran PAI Berbasis Moderasi Beragama Dalam Mencegah Sikap Intoleran Siswa - Suci Satriyanti; Ruslan; Uswatun Hasanah (Universitas Majalengka, 2026)
This study analyzes Islamic Religious Education (PAI) learning strategies based on religious moderation in preventing students’ intolerance. Using a qualitative library research approach, data were collected from accredited journals, books, proceedings, and policy documents related to PAI, religious moderation, and intolerance. Data were analyzed through content analysis, including data reduction, display, and conclusion drawing. The findings show that religious moderation in PAI learning is reflected in the values of wasathiyah (moderation), tasamuh (tolerance), i’tidal (justice), and tawazun (balance), integrated into learning objectives, materials, and processes. Effective strategies include dialogic learning, value habituation, and teacher role modeling, which foster tolerant, inclusive, and respectful student attitudes toward diversity. The study concludes that integrating religious moderation into PAI learning can serve as a preventive educational strategy against intolerance and support character education policies. However, this study is limited to literature analysis without empirical field testing, so further research is needed in real educational contexts.